A multi-stakeholder approach to eHealth development: Promoting sustained healthy living among cardiovascular patients. (March 2021) - Breeman, Linda D.; Keesman, Mike; Atsma, Douwe E.; Chavannes, Niels H.; Janssen, Veronica; van Gemert-Pijnen, Lisette; Kemps, Hareld; Kraaij, Wessel; Rauwers, Fabienne; Reijnders, Thomas; Scholte op Reimer, Wilma; Wentzel, Jobke; et al.
Highlights: Stakeholder involvement in eHealth design can be at micro, meso and macro level. Creating 'one-size-fits-all' applications may be of little value to stakeholders. In contrast, stakeholders may prefer a platform integrating various interventions. Interventions should be matched and tailored to personal preferences. Abstract: Background: Healthy living is key in the prevention and rehabilitation of cardiovascular disease (CVD). Yet, supporting and maintaining a healthy lifestyle is exceptionally difficult and people differ in their needs regarding optimal support for healthy lifestyle interventions. Objective: The goals of this study were threefold: to uncover stakeholders' needs and preferences, to translate these to core values, and develop eHealth technology based on these core values. Our primary research question is: What type of eHealth application to support healthy living among people with (a high risk of) CVD would provide the greatest benefit for all stakeholders? Methods: User-centered design principles from the CeHRes roadmap for eHealth development were followed to guide the uncovering of important stakeholder values. Data were synthesized from various qualitative studies (i.e., literature studies, interviews, think-aloud sessions, focus groups) and usability tests (i.e., heuristic evaluation, cognitive walkthrough, think aloud study). We also developed an innovative application evaluation tool to perform a competitor analysis on 33 eHealth applications. Finally, to make sure to take into account all end-users needs and preferences in eHealth technology development, we created personas and a customer journey. Results: We uncovered 10 universal values to which eHealth-based initiatives to support healthy living in the context of CVD prevention and rehabilitation should adhere to (e.g., providing social support, stimulating intrinsic motivation, offering continuity of care). These values were translated to 14 desired core attributes and then prototype designs. Interestingly, we found that the primary attribute of good eHealth technology was not a single intervention principle, but rather that the technology should be in the form of a digital platform disseminating various interventions, i.e., a 'one-stop-shop'. Conclusion: Various stakeholders in the field of cardiovascular prevention and rehabilitation may benefit most from utilizing one personalized eHealth platform that integrates a variety of evidence-based interventions, rather than a new tool. Instead of a one-size-fits-all approach, this digital platform should aid the matchmaking between patients and specific interventions based on personal characteristics and preferences.